Designing KwaThema: Cultural Inscriptions in the Model Township. Issue 2 (4th March 2019) - le Roux, Hannah
Abstract : Designed at South Africa's National Building Research Institute in 1951, the Witwatersrand township of KwaThema and its NE51 housing models profoundly influenced apartheid's subsequent housing for black Africans. Its schematic layout and many of its physical dimensions were replicated through the medium of the Minimum Standards of Accommodation document that governed later townships. Yet, despite its significance as a model, there is scant documentation of KwaThema as a specific project embedded with design intentionality. Its houses referenced colonial and modernist precursors but transcended these types, as the young NBRI architect–researchers, drawing on experiences of indigenous space and subjects, considered other-than-modern spatiality and its capacity for change. By retrieving marginal evidence from their parallel research projects, this narrative of the first stage of the township's design considers Barrie Biermann's interest in hybrid Cape housing vernaculars, Betty Spence's documentation of indigenous spatial cultures, and Douglas Calderwood's consideration of labour and landscape. Given the spatial potentials latent in these references, it suggests that the generic and specific design histories of KwaThema should be restored and brought into conversation with each other and with the subsequent lived realities of the township that they informed.